Impact of Social Media Based Brand Community Participation on Brand Image in Bangladesh: Mediating Role of Brand Association and Brand Awareness (Global Journal of Management and Business Research, 2023)
The study's objective is to investigate the impact of Social Media-Based Brand Community Participation on the brand's image. Besides, the study also focuses on uncovering the mediating role of brand association and brand awareness. For achieving the above objectives, relevant pieces of literature were extensively studied, and seven hypotheses were developed. For collecting relevant data for the research, a structured questionnaire was developed and administered through using online social media. The study used convenience sampling to collect data from 445 customers who have access to social media platforms and who have participated in several fashion brands' fan pages. The study discovered that Social Media-Based Brand Community Participation (SMBBCP) is positively related to brand association and brand awareness; however, it has an insignificant relationship with brand image. Besides, the brand association is positively associated with brand image, whereas brand awareness has a positive impact on brand association.
Keywords: Brand community participation; Brand association; Brand image; Brand awareness; Fashion brands; Bangladesh